EFEKTIVITAS PROJECT BASED LEARNING DALAM MENINGKATKAN KREATIVITAS SISWA PADA MATA PELAJARAN IPAS DI KELAS V SD NEGERI JATIPECARON KABUPATEN GROBOGAN - Yolanda Tasya Putri Jasmine; Qoriati Mushafanah; Eka Sari Setianingsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The background that prompted this research was that the IPAS learning process in grade V at Jatipecaron Elementary School was still dominated by conventional methods. The negative impact of this method caused students to become passive and find it difficult to develop ideas. To overcome the problem of low student creativity, the researcher considered it necessary to innovate teaching methods. The Project Based Learning (PjBL) model is an innovative model that places students at the center of learning activities through real projects. The problem formulation in this study is: How effective is project-based learning in increasing student creativity in IPAS subjects in grade V at Jatipecaron State Elementary School? The objective of this study is to analyze the effectiveness of the Project-Based Learning (PjBL) model in improving student creativity in IPAS subjects in grade V at Jatipecaron State Elementary School, Grobogan Regency. This study uses a quantitative approach with a Pre-Experimental Design in the form of a One Group Pretest-Posttest Design. The population and sample in this study were all 32 fifth-grade students at Jatipecaron State Elementary School, using a saturated sampling technique. Data were collected through observation, interviews, pretest and posttest instruments to measure learning outcomes and creativity, then analyzed using normality tests and paired sample t-tests. The results showed an increase in student learning outcomes and creativity after the Project Based Learning model was implemented. The average pretest score was 51.7 with a learning completeness of 19%, while the average posttest score increased to 84.4 with a learning completeness of 81%. The normality test results showed that the data was normally distributed (L₀ = 0.112 < Lₜabel = 0.154). The hypothesis test using a paired sample t-test obtained a Sig. (2-tailed) value of 0.000 < 0.05, which means that there was a significant difference between learning outcomes before and after the treatment. Based on the creativity observation results, 41% of students were in the highly creative category. Based on this study, the suggestion is that the Project Based Learning model can be used as an alternative for teachers in teaching to increase student creativity.